Pengembangan Modul Pembelajaran Berbasis Pendekatan Problem Based Learning - Rahmawati Nasser; Aswin Abbas; Saddang Saputra (Jurnal Studi Guru dan Pembelajaran, 2022)
The purpose of this research is to develop learning media in the form of a Statistics Module with a Problem Based Learning (PBL) approach. The Statistics module uses the PBL approach, which is an approach that provides support for developing students’ skills in solving problems in statistics courses due to create enjoyable learning and make students more active than lecturers in the class, not lecturer center anymore. The results of the research conducted in this study are PBL-based statistics course modules (mean, median, and mode) which in the future will be used by students of the Informatics Management Study Program – Academy of Computer Sciences Ternate. The advantage of the PBL-based Statistics module that is used as teaching material is that it makes it easier for students to solve problems in statistics courses and make them more interested in learning them. The PBL-based statistical learning module used as a learning medium can be declared feasible to use based on the results of expert validation and the results of small group module trials. Expert validation is carried out by 2 (two) experts with very appropriate, appropriate, adequate, or inadequate assessment categories. All experts (both) assess if 100% of the module is included in the very feasible category. Whereas for small-scale field trials, 75% of respondents stated that the module was in the very feasible category and 25% of respondents said the module was in the feasible category.